Phytoremediation of Oil-Contaminated Soil by Tagetes erecta L. Combined with Biochar and Microbial Agent - Xin Fang; Pufan Zheng; Haomin Wang; Kefan Wang; Cong Shi; Fuchen Shi (Plants)
Crude oil pollution of soil is an important issue that has serious effects on both the environment and human health. Phytoremediation is a promising approach to cleaning up oil-contaminated soil. In order to facilitate phytoremediation effects for oil-contaminated soil, this study set up a pot experiment to explore the co-application potentiality of Tagetes erecta L. with two other methods: microbial agent and biochar. Results showed that the greatest total petroleum hydrocarbon (TPH) biodegradation (76.60%) occurred in the soil treated with T. erecta, a microbial agent, and biochar; the highest biomass and root activity also occurred in this treatment.GC-MS analysis showed that petroleum hydrocarbon components in the range from C10 to C40 all reduced in different treatments, and intermediate-chain alkanes were preferred by our bioremediation methods. Compared with the treatments with biochar, the chlorophyll fluorescence parameter NPQ_Lss and plant antioxidant enzyme activities significantly decreased in the treatments applied with the microbial agent, while soil enzyme activities, especially oxidoreductase activities, significantly increased. Although the correlation between biochar and most plant growth and soil enzyme activity indicators was not significant in this study, the interaction effect analysis found a synergistic effect between microbial agents and biochar. Overall, this study suggests the co-addition of microbial agents and biochar as an excellent method to improve the phytoremediation effects of oil-contaminated soil and enhances our understanding of the inner mechanism.